Experimental and Numerical Investigation on the Flexural Behavior of Composite-Reinforced Top-Hat Shape Beam - Nima Zahedan; Hamed Ahmadi; Gholam Hossein Liaghat (Mechanics of Advanced Composite Structures)
Top-hat hollow-section beams are widely used in passenger vehicle’s body-in-white structure because of their proper shape for the montage process and also crashworthiness advantages. Hollow section beams with top-hat cross-section are mostly employed in structures like B-pillar, rocker sill, and roof rail which are engaged in side impact collisions. In the present investigation, simplified top-hat beams are developed based on a conventional B-pillar with the aim of improving energy absorption characteristics. Reinforcements are conducted by employing fiber glass-epoxy composite material. Three types of reinforced beams are presented which are either improved by composite-laminating, or by installation of an extra composite-made internal reinforcement. Experimental tests are performed in quasi-static three-point bending condition and based on results, a FE simulation is developed using LS-Dyna explicit code. Specimens are compared based on peak load, total energy absorption (TEA) and specific energy absorption (SEA) amounts. Also, to illustrate the extent of improvements, a not-reinforced top-hat beam is experimentally subjected under three-point bending test. Results depict a significant difference between the performance of beams reinforced by different methods. Comparison between specimens, considering their respective load-displacement diagram and crashworthiness characteristics, show that applying composite laminates to the inside surface of a hat-shaped beam would produce a beam with satisfying flexural behavior.